(3y+1)*27=

Simple and best practice solution for (3y+1)*27= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y+1)*27= equation:


Simplifying
(3y + 1) * 27 = 0

Reorder the terms:
(1 + 3y) * 27 = 0

Reorder the terms for easier multiplication:
27(1 + 3y) = 0
(1 * 27 + 3y * 27) = 0
(27 + 81y) = 0

Solving
27 + 81y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 81y = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 81y = 0 + -27
81y = 0 + -27

Combine like terms: 0 + -27 = -27
81y = -27

Divide each side by '81'.
y = -0.3333333333

Simplifying
y = -0.3333333333

You can always share this solution

See similar equations:

| 35x(-3)= | | 14x+2= | | -3/4+1/4=-7/8*r+3/8*r | | 7x+15=17x-6 | | 2x=8x-12 | | -5(2)+2n= | | 15x-4=7-12x | | -3x-5y=11 | | f/5.25=7.8 | | 56+12v=80+8v | | 6x^2+84+294=0 | | -10(x+4)+56=-24 | | 3(7-a)=12 | | 4xn=1 | | 17x+18=90 | | -1n(x+4)+56=-24 | | 5-10z=-9z-12 | | 1/9w+2/7w=1 | | a/9-2=4 | | y=-4(4)-7 | | 5-19z=-12 | | 6y-15-5y=8 | | p/4-6=-8 | | y=-4(3)-7 | | -8+x/4=12 | | y=-4(2)-7 | | y=-4(1)-7 | | X-19=-2x+10 | | 6(5-g)=18 | | 2y=3x+3 | | y=4(4)-7 | | 3-y=2 | | y=4(3)-7 | | Y=x^2-2x+8 | | 3x-10+x=2 | | y=4(2)-7 | | 12y-5=19 | | y=4(1)-7 | | 16+y/8=20 | | -5=-x+2 | | 1/5x+13+x=1/10(x+40)+4 | | y=-3(4)+0 | | y=-3(3)+0 | | n/4-10=-6 | | y=-3(2)+0 | | 4*2/3+9y=-7 | | y=-3(1)+0 | | (2m-3)(4m+1)= | | y=-3(0)+0 | | x/12+8=10 | | 5x+4=8x+34 | | 5x+4=8x-34 | | (2m-15)(m+1)= | | 10.9-23= | | j/4+3=14 | | x^2+2x+1=43 | | y=3(4)+0 | | 2m^2-13m-15= | | y=3(3)+0 | | 2x+5x-7=35 | | 25(4n^2+1)= | | -7/x-2+1-3x/x | | y=3(2)+0 | | 100n^2+25= | | X+3*2=1 |

Equations solver categories